Women and property rights in Indonesian Islamic legal contexts - Bowen, John R. 1951-; Salim, Arskal (Leiden Studies in Islam and Society, 2018)
In Women and Property Rights in Indonesian Islamic Contexts , eight scholars of Indonesian Islam examine women's access to property in law courts and in village settings. The authors draw on fieldwork from across the archipelago to analyse how judges and ordinary people apply interpretations of law, religion, and gender in deliberating and deciding in property disputes that arise at moments of marriage, divorce, and death. The chapters go beyond the world of legal and scriptural texts to ask how women in fact fare in these contexts. Women's capabilities and resources in Indonesia, the world's largest Muslim society and one with distinctive traditions of legal and social life, provides a critical knowledge base for advancing our understanding of the social life of Islamic law. Contributors: Nanda Amalia, John R. Bowen, Tutik Hamidah, Abidin Nurdin, Euis Nurlaelawati, Arskal Salim, Rosmah Tami andamp; Atun Wardatun.